The effect of tooth loss on the temporomandibular joint space: A CBCT study - Salma Tabatabaei; Maryam Paknahad; Mahdi Poostforoosh (Wiley, 2024)
Abstract Objective The tooth loss has a significant impact on the positioning of the condyle in the glenoid fossa and joint spaces of the temporomandibular joint (TMJ). The aim of this study was to assess the association between tooth loss and TMJ spaces using cone beam computed tomography (CBCT) images. Materials and Methods This retrospective investigation involved the evaluation of CBCT images of the bilateral TMJs in a cohort of 111 individuals, comprising 68 males and 43 women. The dentition of the patients was categorized into three categories, including A (65.4%), B (19.1%), and C (16.4%), based on the Eichner index. Anterior, superior, and posterior joint spaces were then measured in sagittal views. The Kruskal-Wallis test and Mann-Whitney test were employed to identify significant differences among the three Eichner groups. Results The findings of the present study suggested that there was no statistically significant variation in the anterior joint space among different Eichner groups within the general population (p = .781). Nevertheless, the superior and posterior joint spaces exhibited statistically significant alterations, as indicated by p‐values of .039 and .010, respectively. It was detected that condyles were positioned inferiorly and posteriorly in group C when compared to groups A and B. Conclusion The present study indicated that greater loss of tooth‐supporting zones is associated with posterior and inferior displacement of condyles. Understanding these relationships helps emphasize how crucial it is to replace missing teeth to enhance occlusion support and, in turn, stop the progression and further deterioration of temporomandibular disorders.